Phenotype flexibility in wild fish: Dolly Varden regulate assimilative capacity to capitalize on annual pulsed subsidies. (19th March 2013) - Armstrong, Jonathan B.; Bond, Morgan H.; Genner, Martin
Summary Large digestive organs increase rates of energy gain when food is plentiful but are costly to maintain and increase rates of energy loss when food is scarce. The physiological adaptations to this trade‐off differ depending on the scale and predictability of variation in food abundance. Currently, there is little understanding of how animals balance trade‐offs between the cost and capacity of the digestive system in response to resource pulses: rare, ephemeral periods of resource superabundance. We investigated the physiological and behavioural tactics of the fish Dolly Varden (Salvelinus malma) that rear in watersheds with low in situ productivity, but experience annual resource pulses from the spawning migrations of Pacific salmon. The eggs of Pacific salmon provide high‐energy food for Dolly Varden. Dolly Varden sampled 6 weeks prior to the resource pulse exhibited atrophy of the stomach, pyloric caeca, intestine and liver. Throughout the portion of the growing season prior to the resource pulse, fish exhibited empty stomachs, low indices of energy condition and muscle isotope signatures reflecting the previous resource pulse. During the resource pulse, Dolly Varden exhibited large digestive machinery, gorged on salmon eggs and rapidly stored energy in fat reserves, somatic growth and gonad development. Dolly Varden appeared to achieve nearly their entire annual energy surplus during the ∼5‐week period when sockeye salmon spawn. Digestive flexibility provides Dolly Varden the energy efficiency required to survive and reproduce when resource abundance is concentrated into an annual pulse that is predictable, yet highly ephemeral. Although fish are known to incur extremely variable energy budgets, our study is one of the first to document digestive flexibility in wild fish. Our study emphasizes that fish can rely heavily on rare, high‐magnitude foraging opportunities. Human actions that attenuate spikes in food abundance may have stronger than anticipated effects on consumer energy budgets.